Sex allocation based on maternal body size in Japanese barn swallows. Issue 2 (4th March 2018) - Arai, Emi; Hasegawa, Masaru; Ito, Shosuke; Wakamatsu, Kazumasa
Abstract : Sex allocation is the parental resource allocation to sons versus daughters. Given the different benefits and costs of investments in sons and daughters, females should adjust the brood sex ratio according to their own quality to maximize their fitness. In the barn swallow Hirundo rustica, as in many other passerines, females should increase the proportion of sons in their broods with increasing maternal body size, because rearing sons is particularly costly to small females with low feeding capacity, and because reproductive success in the barn swallow, which may depend on rearing conditions, varies more in males. However, evidence supporting this prediction is lacking, even in this model species of sex allocation. Using the Asian subspecies of the barn swallow H. r. gutturalis, we confirmed this prediction. Larger mothers with a longer keel had more sons in their brood. We found that male nestlings invested more in pheomelanin pigmentation compared with female nestlings, while they had shorter wing lengths, indicating that male nestlings are costly to rear compared with female nestlings. Smaller mothers that are at a disadvantage in provisioning may not retard the nestling period by producing daughters, which reduces their parental investment and thus saves their residual reproductive value. This breeding strategy might be particularly beneficial to Japanese barn swallows that breed in environments with high nest predation.